Cover - Nozaki, Thaís; Gonçalves, Sergio Eduardo de Paiva (Brazilian Dental Science, 2018)
Title: Como se ama Illustration Illustrator: Thaís Nozaki Editora Esthamária The Illustration is part of the Brazilian Rhapsody’s libretto, composed by Zélia Marão, produced and presented at CAEB (Eduardo Bonetti Environmental Center).